2014
DOI: 10.3928/1081597x-20140513-01
|View full text |Cite
|
Sign up to set email alerts
|

Surface Quality of Human Corneal Lenticules After SMILE Assessed Using Environmental Scanning Electron Microscopy

Abstract: Using the VisuMax laser to perform SMILE produces smooth cuts absent of surface irregularities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…However, the applicability of these findings is confined to purely myopic corrections because the lenticules did not have cylindrical correction. 47 …”
Section: Safetymentioning
confidence: 99%
“…However, the applicability of these findings is confined to purely myopic corrections because the lenticules did not have cylindrical correction. 47 …”
Section: Safetymentioning
confidence: 99%
“…The highest surface regularity score was achieved using the lowest pulse energy, presenting that lower pulse energy facilitates a smoother cut surface. Furthermore, smoother lenticule surfaces were reported observed using a higher frequency laser [8,21].…”
Section: Discussionmentioning
confidence: 93%
“…Based on the aforementioned investigations, a new generation VisuMax laser with settings of a 500 kHz repetition rate and a pulse energy of 130 nJ was investigated. Researchers studied the scan quality of corneal lenticules in the context of myopia treatment using the new laser system, and found that both sides of the lenticules exhibited smooth surfaces [21]. Therefore, in the current study, the exact same laser settings were used to perform hyperopia correction in SMILE, and enabled homogeneous cutting.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, smoother lenticule surfaces were reported observed using a higher frequency laser. [18,8] Based on the aforementioned investigations, a new generation VisuMax laser with settings of a 500 kHz repetition rate and a pulse energy of 130 nJ was investigated. Researchers studied the scan quality of corneal lenticules in the context of myopia treatment using the new laser system, and found that both sides of the lenticules exhibited smooth surfaces.…”
Section: Discussionmentioning
confidence: 99%